APPROACHES TO TEACHING ESL ACADEMIC WRITING: A MULTIPLE CASE STUDY (Malaysian Journal of Learning and Instruction, 2025)
Purpose - Academic writing skills are fundamental for students at tertiary level. Possessing these skills can aid students in their studies as they are mostly assessed based on their proficiency in writing skills. Due to this, the teaching of English academic writing has become pivotal for English as a second language (ESL) lecturers in ensuring students’ abilities to write academically, while at the same time achieving the course learning outcomes. Therefore, this study aims to explore the teaching approaches employed by ESL lecturers in teaching English academic writing at Malaysian universities.Methodology - Grounded in a multiple case study, four ESL lecturers from four different universities (i.e., two public and two private universities) were purposively selected as the research participants. Data collection was done through in-depth interviews, lesson observations, and document analysis. The data were analyzed thematically using thematic analysis and cross-case analyses which compare differences and similarities across cases.Findings - Findings indicate that Malaysian ESL lecturers at public and private universities employed various teaching approaches, such as teacher-centered traditional approach, process-genre approach, humanistic approach, and collaborative writing approach in teaching English academic writing. These teaching approaches were employed by the ESL lecturers based on their knowledge of pedagogy, teaching experience and exposure to English academic writing, while at the same time adhering to the syllabus of their universities when catering to various students’ writing proficiency.Significance – This study provides insightful guidance to ESL/EFL lecturers teaching English academic writing. The findings will help them to select suitable teaching approaches to meet their students’ needs, proficiency levels and to achieve learning objectives. ESL lecturers are also urged to enhance their content, pedagogical, and technological pedagogical content knowledge in meeting the needs of 21st century students.